Amoxicillin-loaded hydroxyapatite-enriched scaffolds for drug release and guided bone regeneration - ŞENGÖR, MUSTAFA (My University, 2023)
The design of scaffolds for controlled drug release in bone tissue engineering requires careful consideration of several factors. Scaffold degradation and drug diffusion within the polymer matrix, influenced by pore size and distribution, must be carefully considered in the design of composite scaffolds. In this study, multi-functional scaffolds containing different amounts of hydroxyapatite (0, 0.25, 0.5, 1 % wt/wt) were prepared and characterised in terms of their chemical and morphological properties, as well as their drug release capabilities. Amoxicillin was used as a model drug to investigate the kinetic release model of the scaffolds, which were created using a freeze-dry method to form a spongy structure. Image processing techniques were used to measure the surface pore sizes and distributions. The results showed that the 0.5 wt. % hydroxyapatite-added scaffold had the smallest size, with an average pore size of 7 +/- 4.3 mu m and a weight loss of 45 %. All the prepared scaffolds fit Hills kinetic model. The best fitting one was observed in the 0.5 wt. % addition. By carefully considering all the factors, it is possible to optimise the release of the drug from the polymeric material and the degradation characteristics to improve its performance.
Keywords: Mühendislik ve Teknoloji; Engineering and Technology; MALZEME BİLİMİ, SERAMİK; Malzeme Bilimi; Mühendislik, Bilişim ve Teknoloji (ENG); MATERIALS SCIENCE, CERAMICS; MATERIALS SCIENCE; Engineering, Computing & Technology (ENG); Seramik ve Kompozitler; Genel Malzeme Bilimi; Fizik Bilimleri; Ceramics and Composites; General Materials Science; Physical Sciences; Hydroxyapatite; Bioceramics; Drug release; Porosity